GENESIS CONTRADICTIONS OF GENDER APPROACH IN EDUCATION OF CHILDREN - Zh. N. Dyuldina; A. Yu. Skorobogatova (Obrazovanie i Nauka)
The aim of the investigation is to consider genesis contradictions of gender approach in modern education and training of children and possibilities of its application in an educational system during the newest period of the society development.Methods, results and scientific novelty. The retrospective analysis of the sources has shown that gender approach isn’t new and not studied: on the contrary, separate education and training of boys and girls in the past was a norm and a duty of parents and teachers. However, the reflection of social processes shows the demolition of traditional system of gender stratification; weakening of women’s and men’s polarization of social roles; change of cultural stereotypes of masculinity and femininity; objective changes in the matrimonial relations. Everything listed above brings into focus an investigative search of new approaches to gender education. The essence of the terms «gender», «gender approach» is specified. Despite very long history of gender education (which was cultivated since the most ancient eras of existence of a mankind), insufficient study of this problem is stated now. Special importance of gender aspect in family education is emphasized. The different points of view in understanding of gender approach in modern science are revealed; the main perspective directions of researches on this subject are noted.Practical significance. The materials of the present article can be used in teaching history of pedagogics, gender psychology and gender pedagogics.